2011
DOI: 10.1111/j.1444-0938.2010.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of blood pressure in glaucoma

Abstract: Although intraocular pressure (IOP) remains an important risk factor for glaucoma, it is clear that other factors can also influence disease development and progression. More recently, the role that blood pressure (BP) has in the genesis of glaucoma has attracted attention, as it represents a clinically modifiable risk factor and thus provides the potential for new treatment strategies beyond IOP reduction. The interplay between blood pressure and IOP determines the ocular perfusion pressure (OPP), which regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 166 publications
(266 reference statements)
3
110
0
4
Order By: Relevance
“…[33][34][35] A complete description of the theory how low OPP may be involved in glaucoma pathogenesis has been summarized in recent reviews. 36,37 With regard to the present data, it is of interest that ONHBF appears to have relatively little regulatory capacity when IOP is increased.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] A complete description of the theory how low OPP may be involved in glaucoma pathogenesis has been summarized in recent reviews. 36,37 With regard to the present data, it is of interest that ONHBF appears to have relatively little regulatory capacity when IOP is increased.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is the compromised blood supply to the optic nerve due to mechanical compression exerted by high IOP. There is evidences that suggests tissue hypoxia in the retina may affect the survival ganglion cells (He et al, 2011;Tezel and Wax, 2004). Other hypothesis includes oxidative or nitrative stress, both at the level of trabecular meshwork (Sacca et al, 2007) and 21 retinal ganglion cells (Aslan et al, 2008;Tezel, 2006); autoimmune reactions in which an individual's immune system facilitate somatic/axonal degeneration of retinal ganglion cells (Wax and Tezel, 2009); glutamate toxicity (Vorwerk et al, 1999); loss of neurotrophic factors (Pease et al, 2000), etc.…”
Section: Pathogenesis Of Glaucomamentioning
confidence: 99%
“…3,9 Patients at both extremes of blood pressure spectrum show an increased prevalence of glaucoma. 10,11 The incidence is more for high-tension glaucoma. 12 Recent studies have also demonstrated that the effects on the visual field due to elevation of intraocular pressure was related to diastolic ophthalmic artery pressure.…”
Section: Resultsmentioning
confidence: 99%